Gender Differences in Online Learning - Idrizi, Ermira; Filiposka, Sonja; Trajkovikj, Vladimir (My University, 2020)
Online learning is proving to be a new milestone in education, the ad- vantages that were known from the beginning are now days more appealing and important than ever, the opportunity to learn and teach not depended on location and time and has brought online learning in front of each education institution. We will focus on one dimension of how online learning impacts academic suc- cess based on gender. Gender has always been an interest since we assume that male and female students vary in their environment of learning and especially online, with a promising advantage for male students since it is assumed that male students would be better handling the technical part, than female students. We conducted two online courses on the Moodle platform, and observed how gender will influence students' outcomes. The initial results show little differences based on gender where male students slightly have higher results in only online courses while female students show higher overall success for the Faculty of Computer Science.
Keywords: Gender Online learning, Preferred materials